Hubungan antara kombinasi hemodialisis (hd)/ hemoperfusi (hp) dengan status nutrisi (7 point subjective global assessment (sga) dan Albumin serum) pasien hemodialisis regular - Dwi Bayu Wikarta; Alwi Thamrin Nasution; Abdurrahim Rasyid Lubis (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Background : Malnutrition in hemodialysis patients is common and it’s a regular independent factors affecting morbidity and mortality. This relates to the level of uremic toxins clearance during the process of hemodialysis is less than optimal. Clinical Application of hemoperfusion combination with hemodialysis (HD/HP) demonstrated the optimal clearance in molecular uremic toxins clearance. Kidney Disease Outcomes Quality Initiative (KDOQI) recommends assessment nutritional status of regular hemodialysis patients with a combination of valid assessment tools. such as 7-point SGA (Subjective Global Assessment) and albumin. This aim of the study to determine correlation between the combination of HD/HP with the nutritional status of regular hemodialysis patients.Method : This prospective cohort study from December 2013 to March 2014 on 20 regular hemodialysis patient and do history. measurements of height. weight. body mass index. nutritional status assessment by 7-point SGA and examination of serum albumin.Results : At the end of observation. 20 subjects were observed one subject out of the study. There is a significant difference between the mean of 7-point SGA score before and after combination hemodialysis/hemoperfusion (p<0.05). There is a significant difference between the mean albumin before and after first combination Albumin HD/HP (p<0.05). There is a strong relationship between the 7-point SGA with BMI after combination (r=0.636.p<0.01).Conclusion : The combination of HD / HP is good clinical application for the treatment of malnutrition in regular hemodialysis patients. Regular assessment of nutritional status of regular hemodialysis patients is necessary. with a combination of a valid assessment tool (7-point SGA. albumin) is expected to help decrease morbidity and mortality.Key word : Hemodialysis; haemoperfusion; 7-point SGA; albumin